2020
DOI: 10.31234/osf.io/gbdn8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

When Private Optimism meets Public Despair: Dissociable effects on behavior and well-being

Abstract: When faced with a threat, peoples’ estimate of risk guides their response. When danger is to the self as well as to others two estimates are generated: the risk to oneself and the risk to others. As these estimates likely differ, it is unclear how exactly they drive a response. To answer this question, we studied a large representative sample of Americans facing the COVID-19 pandemic at two time points (N1=1145, N2=683). We discover a paradoxical duality: a tendency to be optimistic about one’s own risk of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…Participants completed an online survey which lasted approximately 30 minutes. In addition to the questions that formed this study, additional information was gathered as part of parallel studies conducted by members of our lab (e.g., Globig et al, 2020). These focused mostly on habits, personality, psychopathology and other opinions regarding the crisis.…”
Section: Methodsmentioning
confidence: 99%
“…Participants completed an online survey which lasted approximately 30 minutes. In addition to the questions that formed this study, additional information was gathered as part of parallel studies conducted by members of our lab (e.g., Globig et al, 2020). These focused mostly on habits, personality, psychopathology and other opinions regarding the crisis.…”
Section: Methodsmentioning
confidence: 99%
“…Optimism, hope, and self-efficacy are three cognitive variables representing positive expectations that proved to protect against development of PTSD (Gallagher, Long, & Phillips, 2020) and which may be helpful in overcoming psychological consequences of COVID-19-related stress. We found two studies which examined different types of optimism in the context of COVID-19-related stress and well-being (Arslan & Yildirim, 2020;Globig et al, 2020). Globig, Blain & Sharot (2020) discovered that optimism regarding the COV-ID-19 pandemic was associated with people's positive feelings and this association was mediated by people's sense of agency over their future.…”
Section: Psychological Factorsmentioning
confidence: 99%
“…We found two studies which examined different types of optimism in the context of COVID-19-related stress and well-being (Arslan & Yildirim, 2020;Globig et al, 2020). Globig, Blain & Sharot (2020) discovered that optimism regarding the COV-ID-19 pandemic was associated with people's positive feelings and this association was mediated by people's sense of agency over their future. Arslan and Yildirim's study (2020) indicated that optimistic cognitions and psychological inflexibility mediated the effect of coronavirus stress on psychological problems.…”
Section: Psychological Factorsmentioning
confidence: 99%
See 2 more Smart Citations